Prevalence and influencing factors of posttraumatic growth among nurses suffering from workplace violence: A cross‐sectional study. (12th March 2022) - Zeng, Li; Zhang, Xiangeng; Wang, Fang; Yun, Jie; Lai, Li; Jin, Man; Liu, Guiling; Qiu, Yinong; Wang, Jialin
ABSTRACT: The purpose of this study was to (i) identify the level of posttraumatic growth among nurses suffering from workplace violence, (ii) clarify the relationship between nurses' posttraumatic growth and compassion satisfaction, burnout, secondary traumatic stress, and (iii) determine the influencing factors for posttraumatic growth among nurses suffering from workplace violence. A cross‐sectional study was conducted to investigate 726 nurses suffering from workplace violence in 10 tertiary hospitals by using demographic, work‐related information, lifestyle questionnaire, simplified Chinese version of the Posttraumatic Growth Inventory, and professional quality of life scale. In the findings, (i) the participants' posttraumatic growth scores were 57.29 ± 21.56, while the compassion satisfaction, burnout, and secondary traumatic stress scores were 32.82 ± 6.80, 27.17 ± 5.53, and 26.67 ± 5.29, respectively, (ii) posttraumatic growth was positively correlated with compassion satisfaction and secondary traumatic stress, and negatively correlated with burnout, and (iii) compassion satisfaction, sleep hours per day, department, scheduling, alcohol, secondary traumatic stress, children, and work hours per day were influencing factors of posttraumatic growth, which explained 36.3% of the total variance. Our study indicates that Chinese nurses may experience moderate levels of compassionate satisfaction, burnout, secondary traumatic stress, and low levels of posttraumatic growth after suffering from workplace violence, while the posttraumatic growth of nurses suffering from workplace violence is more affected by work‐related variables and lifestyle‐related variables, but less affected by other sociodemographic variables. Therefore, it is necessary to strengthen the psychological evaluation of nurses and adopt targeted strategies to promote nurses' posttraumatic growth.